Learning the Values of Aswaja An-Nahdliyah for Santri MBI Amanatul Ummah Pacet Mojokerto - Rasyid, Aryadi Ahmad; Kholis, Mohammad Maulana Nur (Anjasmoro: Islamic Interdisciplinary Journal, 2024)
Learning the values ​​of Aswaja (Ahlussunnah wal Jama'ah) which are Islamic religious teachings held by Nahdlatul Ulama (NU), the largest Islamic organization in Indonesia, has a significant influence on people's religious and cultural understanding. An-Nahdliyah refers to the values ​​contained in Islamic teachings practiced by members of Nahdlatul UlamaThe purpose of this research: first, to analyze the values ​​of Aswaja An-Nahdliyah which are carried out at the International Standard Madrasah Aliyah (MBI) Amanatul Ummah Pacet - Mojokerto. Second, to analyze the learning of Aswaja An-Nahdliyah values ​​among students at the Standard Aliyah Madrasah International (MBI) Amanatul Ummah Pacet – Mojokerto. Third to identify obstacles and provide solutions in learning Aswaja An-Nahdliyah values ​​for students at the International Standard Madrasah Aliyah (MBI) Amanatul Ummah Pacet – Mojokerto. By using qualitative research and a case study approach. Data collection techniques use interviews, observation, and documentation. The data sources are informants who are directly involved in the implementation of Mujadi activities, namely the Deputy Mujadi Curriculum Coordinator, the Deputy Mujadi Teacher Coordinator, Aswaja teachers, and students. The results of the research that have been studied by the authors are first, tasamuh, tawasuth, tawazun, and amar ma'ruf nahi munkar which are reflected in the daily activities of students at this institution such as inviting national and international scholars, practicing amaliyah, and in relationships. students' social life. Second, on learning the values ​​of Aswaja An-Nahdliyah it was explained that it had been instilled in students from the moment they entered this institution, but only limited to learning in terms of the practice of amaliyah, and when they reached the final semester, they were given aswaja materials. Third supporting and inhibiting factors such as lack of discipline from students, limited attention to students as a whole, and limited time to provide deeper understanding to students. The solution is to improve the quality of teachers, invite ulama or experts in the field, use diverse learning approaches to meet the diverse learning needs of students, and link the teachings of Aswaja An-Nahdliyah to the context of students' daily lives.